Limited hair cell induction from human induced pluripotent stem cells using a simple stepwise method. (10th July 2015) - Ohnishi, Hiroe; Skerleva, Desislava; Kitajiri, Shin-ichiro; Sakamoto, Tatsunori; Yamamoto, Norio; Ito, Juichi; Nakagawa, Takayuki
Highlights: Hair cell-like cells were induced from human iPS cells by a simple stepwise method. Hair cell-like cells were induced from human iPS cells using no xenogeneic cells. Treatment with bFGF induced otic placodal cells but had limited efficiency. Abstract: Disease-specific induced pluripotent stem cells (iPS) cells are expected to contribute to exploring useful tools for studying the pathophysiology of inner ear diseases and to drug discovery for treating inner ear diseases. For this purpose, stable induction methods for the differentiation of human iPS cells into inner ear hair cells are required. In the present study, we examined the efficacy of a simple induction method for inducing the differentiation of human iPS cells into hair cells. The induction of inner ear hair cell-like cells was performed using a stepwise method mimicking inner ear development. Human iPS cells were sequentially transformed into the preplacodal ectoderm, otic placode, and hair cell-like cells. As a first step, preplacodal ectoderm induction, human iPS cells were seeded on a Matrigel-coated plate and cultured in a serum free N2/B27 medium for 8 days according to a previous study that demonstrated spontaneous differentiation of human ES cells into the preplacodal ectoderm. As the second step, the cells after preplacodal ectoderm induction were treated with basic fibroblast growth factor (bFGF) for induction of differentiation into otic-placode-like cells for 15 days. As the final step, cultured cells were incubated in a serum free medium containing Matrigel for 48 days. After preplacodal ectoderm induction, over 90% of cultured cells expressed the genes that express in preplacodal ectoderm. By culture with bFGF, otic placode marker-positive cells were obtained, although their number was limited. Further 48-day culture in serum free media resulted in the induction of hair cell-like cells, which expressed a hair cell marker and had stereocilia bundle-like constructions on their apical surface. Our results indicate that hair cell-like cells are induced from human iPS cells using a simple stepwise method with only bFGF, without the use of xenogeneic cells.